2015
DOI: 10.1159/000430393
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 Inhibits Apoptosis of Pulmonary Endothelial Cells During Acute Lung Injury Through Suppressing MiR-4262

Abstract: This is an Open Access article licensed under the terms of the Creative Commons AttributionNonCommercial 3.0 Unported license (CC BY-NC) (www.karger.com/OA-license), applicable to the online version of the article only. Distribution permitted for non-commercial purposes only. Abstract Background/Aims: Angiotensin converting enzyme 2 (ACE2) treatment suppresses the severity of acute lung injury (ALI). The effects of ACE2 in ALI have been shown to not only result from its antagonizing hydrolyzing angiotensin II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…Recently, we and others have shown that ACE2 has therapeutic effects on ALI, seemingly through different mechanisms, e.g. suppression of apoptosis of PECs [20][21][22][23][24][25][26]. However, a role of ACE2 in antagonizing VEGFa-mediated increases in lung vessel permeability in ALI has not been acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others have shown that ACE2 has therapeutic effects on ALI, seemingly through different mechanisms, e.g. suppression of apoptosis of PECs [20][21][22][23][24][25][26]. However, a role of ACE2 in antagonizing VEGFa-mediated increases in lung vessel permeability in ALI has not been acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the aberrant expression of miRNAs is involved in modulating endothelial apoptosis [33-35]. In this study, a microarray analysis was performed in pHUVEC treated with stearic acid, which identified miR-1185 as highly up-regulated among a panel of 48 up-regulated miRNAs.…”
Section: Discussionmentioning
confidence: 96%
“…Since bleomycin induces lung tissue-specific damage that leads to fibrosis in certain cancer patients and in different animal models [49-51], our results would predict that the GAGs at lung epithelial cells might facilitate bleomycin uptake. Such experiment is currently conducted in our laboratory in a bleomycin-induced fibrosis mouse model.…”
Section: Discussionmentioning
confidence: 99%